2023
DOI: 10.1136/bmjopen-2022-063198
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation of tofacitinib and TNF inhibitors in patients with rheumatoid arthritis: analysis of pooled data from two registries in Canada

Abstract: ObjectivesThe similarity in retention of tumour necrosis factor inhibitors (TNFi) and tofacitinib (TOFA) was previously reported separately by the Ontario Best Practices Research Initiative and the Quebec cohort Rhumadata. However, because of small sample sizes in each registry, we aimed to confirm the findings by repeating the analysis of discontinuation of TNFi compared with TOFA, using pooled data from both these registries.DesignRetrospective cohort study.SettingPooled data from two rheumatoid arthritis (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…We then showed that none of the potential predictors of therapy discontinuation considered, including patient age, previous treatment with biologics, concomitant use of csDMARD, and positivity for RF and/or ACPA, were statistically significant after regression analysis. Similar data were reported by Bilgin et al [ 33 ], Movahedi et al [ 34 ], Bird et al [ 35 ], and Finckh et al [ 36 ], who found no relevant predicting factor for TOFA discontinuation. Our results are also in agreement with a recently published paper analyzing data from a Korean registry, in which no predictive factors for discontinuation of therapy were found, except RF and ACPA positivity, both of which were associated with higher drug retention rates [ 37 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We then showed that none of the potential predictors of therapy discontinuation considered, including patient age, previous treatment with biologics, concomitant use of csDMARD, and positivity for RF and/or ACPA, were statistically significant after regression analysis. Similar data were reported by Bilgin et al [ 33 ], Movahedi et al [ 34 ], Bird et al [ 35 ], and Finckh et al [ 36 ], who found no relevant predicting factor for TOFA discontinuation. Our results are also in agreement with a recently published paper analyzing data from a Korean registry, in which no predictive factors for discontinuation of therapy were found, except RF and ACPA positivity, both of which were associated with higher drug retention rates [ 37 ].…”
Section: Discussionsupporting
confidence: 88%
“…It has been reported from a Turkish study, in which the TOFA retention rate was 63.9% at 1 year [ 33 ]. In another study, Movahedi et al found a drug retention rate of 63.3% at a mean follow-up of 23.2 months [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an observational cohort study, patients with RA receiving JAKis did not demonstrate higher rates of discontinuation owing to AEs than those treated with tumor necrosis factor inhibitors (TNFi) did [ 22 ]. In contrast, higher discontinuation rates owing to AEs were observed with tofacitinib than with TNFis in older patients having RA with cardiovascular risk factors [ 23 ]. It was reported that RA with lower cerebrovascular attack-free survival rates had highest disease activity levels at baseline [ 24 ].…”
Section: Discussionmentioning
confidence: 99%